Comparative analysis reveals distinct floral scent patterns in three Durio species - CHUAH YEAN MAE; NUR FARIZA M. SHAIPULAH; MOHAMED NOR ZALIPAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Mae CY, Shaipulah NFM, Zalipah MN. 2025. Comparative analysis reveals distinct floral scent patterns in three Durio species. Biodiversitas 26: 3136-3143. The floral scents of three durian species were collected using the dynamic headspace method and analyzed by Gas Chromatography-Mass Spectrometry (GC-MS). A total of 52 volatile compounds from nine different chemical classes were detected from Durio zibethinus, D. lowianus, and D. graveolens flowers. The floral profiles of D. zibethinus were dominated by alkanes and sesquiterpenes, whereas those of D. lowianus and D. graveolens were dominated by triterpenes and sesquiterpenes, respectively. The hexane eluates extracted more sesquiterpenes than hexane:ethyl acetate eluates. In D. zibethinus flowers, squalene was identified as the predominant volatile compound in hexane extracts, while ?-caryophyllene dominated in hexane:ethyl acetate extracts. Squalene was the primary volatile component in hexane extracts of D. lowianus flowers, whereas (E,E)-?-farnesene predominated in the hexane:ethyl acetate fraction. (E,E)-?-farnesene was the dominant volatile compound emitted from D. graveolens flowers, prevailing in both hexane and hexane:ethyl acetate extracts. Sulfur-containing compounds were absent from all three species. The diverse terpene composition, bright red petals, and extended flowering period of D. lowianus suggest a generalist strategy targeting multiple pollinator groups across both day and night. This study revealed different pollination strategies among three durian species through their distinct floral volatile profiles, highlighting the intricate and multifaceted nature of plant-pollinator relationships in tropical ecosystems.